ANALISIS KEMAMPUAN KOGNITIF SISWA PADA MATERI PEMANASAN GLOBAL DI SMA PERSIAPAN STABAT - Haryati; Anisa Noverita; Unita Sukma Zuliani Nasution; Eka Darliana; Tya Astuti (LPPM STKIP AL MAKSUM, 2025)
This study focuses on